Abrupt termination of the 2012 Pacific warming and its implication on ENSO prediction. Issue 24 (16th December 2014) - Su, Jingzhi; Xiang, Baoqiang; Wang, Bin; Li, Tim
Abstract In the summer of 2012, there was a clear signal of the developing El Niño over the equatorial Pacific, and many climate models forecasted the occurrence of El Niño with a peak phase in the subsequent winter. However, the warming was aborted abruptly in late fall. Here we show that the abrupt termination of the 2012 Pacific warming was largely attributed to the anomalous sea surface temperature (SST) cooling in the northeastern and southeastern subtropical Pacific. The anomalous SST cooling induced strong easterly and low‐level divergence anomalies, suppressing the development of westerly and convection anomalies over the equatorial central Pacific. Thus, the surface warming over the equatorial Pacific was decoupled from the surface wind forcing and subsurface thermocline variability, inhibiting its further development into a mature El Niño in the winter of 2012–2013. This study highlights the importance of the SST anomaly in the subtropical Pacific in El Niño prediction.